2019
DOI: 10.20471/acc.2019.58.02.11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Occupational Stress on the Activation of Hemostatic and Inflammatory System

Abstract: SUMMARYA 24-hour shift is one of the major stressors for physicians because, apart from causing fatigue and circadian rhythm disorders, it often requires making vital decisions for patients within a short time frame. It is known that workplace stress leads to the activation of the coagulation system, which can result in imbalance of the coagulation and fibrinolysis system. The state of stress can also generate proinflammatory mediators. The aim of this study was to examine the effect of 24-hour shift on global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…It is possible that the unusually high amount of PCs included in the OO consumption sustained for three weeks could be responsible for the unexpected effect in CRP. CRP levels have also been shown to raise when circadian rhythm is altered [136], in type-2 diabetes [137], and with dietary habits or fast/fed status [138], factors that might have contributed to the observed increase in CRP. Another randomized controlled trial which tested an OOPC-enriched VOO in pre-/hypertensive individuals in a postprandial situation, demonstrated that this treatment improved proinflammatory biomarkers such as VCAM-1 and PAI-1.…”
Section: Effects Of Olive Oil Phenolic Compounds On Gut Microbiota Anmentioning
confidence: 99%
“…It is possible that the unusually high amount of PCs included in the OO consumption sustained for three weeks could be responsible for the unexpected effect in CRP. CRP levels have also been shown to raise when circadian rhythm is altered [136], in type-2 diabetes [137], and with dietary habits or fast/fed status [138], factors that might have contributed to the observed increase in CRP. Another randomized controlled trial which tested an OOPC-enriched VOO in pre-/hypertensive individuals in a postprandial situation, demonstrated that this treatment improved proinflammatory biomarkers such as VCAM-1 and PAI-1.…”
Section: Effects Of Olive Oil Phenolic Compounds On Gut Microbiota Anmentioning
confidence: 99%
“…In our study, a strong correlation was found in the rate of sleep disturbances between morning shift workers and those participants working a rotating shift system. Shift working nurses find it stressful to deal with the combination of family-home environment, their responsibilities in caring for children, and night shifts 27 . Night shift after full day work at home does not allow sufficient time for rest and sleep, and our study found that shift work nurses more frequently used sleeping pills, which is consistent with the results of other studies [24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory markers were attributed to increased job strain within this cohort which demonstrates the importance of decreased rest and increased physical inactivity as stressors on shift work-driven inflammation. A more recent experimental study looked at 60 resident physicians aged 25-35 working 24-hour shifts [ 39 ]. CRP was measured via phlebotomy and found to be significantly greater in individuals after a 24-hour shift compared to those after an eight-hour working shift (1.57 mg/L vs. 0.79 mg/L) (p = 0.024).…”
Section: Reviewmentioning
confidence: 99%